2015
DOI: 10.1016/j.ssnmr.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lithium ion dynamics in Li2S+GeS2+GeO2 glasses studied using 7Li NMR field-cycling relaxometry and line-shape analysis

Abstract: We use (7)Li NMR to study the ionic jump motion in ternary 0.5Li2S+0.5[(1-x)GeS2+xGeO2] glassy lithium ion conductors. Exploring the "mixed glass former effect" in this system led to the assumption of a homogeneous and random variation of diffusion barriers in this system. We exploit that combining traditional line-shape analysis with novel field-cycling relaxometry, it is possible to measure the spectral density of the ionic jump motion in broad frequency and temperature ranges and, thus, to determine the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The detection fields amounted to 42 and 28 MHz in the former and latter cases, respectively. The temperature was controlled with a flow cryostat for gaseous nitrogen and stabilized on ±0.2 K with a total accuracy of 1 K. Further experimental details of our 1 H and 7 Li FC approaches can be found in previous works. , …”
Section: Methodsmentioning
confidence: 99%
“…The detection fields amounted to 42 and 28 MHz in the former and latter cases, respectively. The temperature was controlled with a flow cryostat for gaseous nitrogen and stabilized on ±0.2 K with a total accuracy of 1 K. Further experimental details of our 1 H and 7 Li FC approaches can be found in previous works. , …”
Section: Methodsmentioning
confidence: 99%
“…While MAS is extremely useful at determining the local structure of glassy materials, alternate methods such as relaxometry can probe the Li ion dynamics at various timescales [14]. Marple et al studied the Li-ion dynamics of Chalcogenide Glasses, composed of Li2S, Ga2Se3, and GeSe2 (LGGS) in mixed compositions, ranging from 7.5% to 50% Li [15,16].They performed electrochemical impedance spectroscopy (EIS) to find ionic conductivities as a function of both composition and temperature, and extracted Li ion activation energies from the subsequent Arrhenius plots.…”
Section: Techniques In Nuclear Magnetic Resonancementioning
confidence: 99%
“…It is known that combinations of glass formers can lead to anomalously ionic conductivities, hereafter referred to as the "mixed glass former effect" (MGFE) [12,14,[18][19][20]. This effect can either drastically increase or decrease ionic conductivity, known as the positive and negative MGFE, Plotting the 7 Li NMR lineshapes for each glass reveals a characteristic sigmoid shape.…”
Section: Techniques In Nuclear Magnetic Resonancementioning
confidence: 99%
“…In particular, 7 Li spin-lattice relaxation (SLR) analysis has a long-standing tradition in studies of local lithium ion dynamics in solid electrolytes. [13][14][15][16] While traditional approaches used a single or, occasionally, a few magnetic fields B 0 and, thus, Larmor frequencies ω L , recent studies showed that 7 Li field cycling (FC) enables measurements of the SLR time T 1 in a broad continuous range of ω L values, 17,18 providing straightforward access to the frequency-dependent spectral density of the lithium ion jump motion. In addition to these studies of lithium ion dynamics on local scales in homogeneous magnetic fields, 7 Li NMR experiments in magnetic field gradients allow one to observe lithium ion diffusion on mesoscopic scales on the order of 1 µm, in particular, to measure the selfdiffusion coefficient D.…”
Section: -7mentioning
confidence: 99%
“…Motivated by previous FC work, 26 including our 7 Li FC studies, 17,18 we exploit the fluctuation-dissipation relation between the imaginary parts of dynamic susceptibilities and the spectral densities, χ ′′ (ω) = ωJ(ω), and present the results in the form of a generalized 'NMR susceptibiliy' defined as χ…”
Section: 13mentioning
confidence: 99%